Adaptive management intentions with a reality of evaluation: Getting science back into policy - Hasselman, Lyndal (Environmental Science & Policy, 2017)
In Australia’s Murray-Darling Basin water reform has been contentious as government attempts to reconcile historical over allocation of water to irrigation with the use of water for environmental outcomes. However, in many aspects, scientific knowledge of the environment is either imperfect, incomplete or environmental responses are unpredictable, with this uncertainty preventing definitive policy and closure of political arguments. In response to uncertainty and knowledge gaps, adaptive management has been written into the legislation, along with provisions for periodic evaluation. This research ascertains how adaptive management is understood by policy makers, with this indicative of future implementation of adaptive management. The way in which adaptive management is constructed by policy makers is determined through legislation, public speeches, government reports and semi-structured interviews. The findings demonstrate that adaptive management has been subsumed by evaluation. The loss of adaptive management as a distinct concept is seen as a loss of science and discovery from the policy process, with the dominance of evaluation discussed as limiting innovation and reinforcing a ‘muddling through’ of policy.
Keywords: Accountability; Adaptive Management; Evaluation; Science; Uncertainty

Using adaptive processes and adverse outcome pathways to develop meaningful, robust, and actionable environmental monitoring programs - Arciszewski, Tim J.; Munkittrick, Kelly R.; Scrimgeour, Garry J.; Dubé, Monique G.; Wrona, Fred J.; Hazewinkel, Rod R. (Integrated Environmental Assessment and Management, 2017)
The primary goals of environmental monitoring are to indicate whether unexpected changes related to development are occurring in the physical, chemical, and biological attributes of ecosystems and to inform meaningful management intervention. Although achieving these objectives is conceptually simple, varying scientific and social challenges often result in their breakdown. Conceptualizing, designing, and operating programs that better delineate monitoring, management, and risk assessment processes supported by hypothesis-driven approaches, strong inference, and adverse outcome pathways can overcome many of the challenges. Generally, a robust monitoring program is characterized by hypothesis-driven questions associated with potential adverse outcomes and feedback loops informed by data. Specifically, key and basic features are predictions of future observations (triggers) and mechanisms to respond to success or failure of those predictions (tiers). The adaptive processes accelerate or decelerate the effort to highlight and overcome ignorance while preventing the potentially unnecessary escalation of unguided monitoring and management. The deployment of the mutually reinforcing components can allow for more meaningful and actionable monitoring programs that better associate activities with consequences. Integr Environ Assess Manag 2017;13:877–891. © 2017 The Authors. Integrated Environmental Assessment and Management Published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
Keywords: Adaptive monitoring; Environmental management; Environmental monitoring; Tier; Trigger

Participatory adaptive management leads to environmental learning outcomes extending beyond the sphere of science - Fujitani, Marie; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Science Advances, 2017)
Resolving uncertainties in managed social-ecological systems requires adaptive experimentation at whole-ecosystem levels. However, whether participatory adaptive management fosters ecological understanding among stakeholders beyond the sphere of science is unknown. We experimentally involved members of German angling clubs (n = 181 in workshops, n = 2483 in total) engaged in self-governance of freshwater fisheries resources in a large-scale ecological experiment of active adaptive management of fish stocking, which constitutes a controversial management practice for biodiversity and ecosystem functioning when conducted inappropriately. The collaborative ecological experiments spanned several years and manipulated fish densities in 24 lakes with two species. In parallel, we experimentally compared changes in ecological knowledge and antecedents of proenvironmental behavior in stakeholders and managers who were members of a participatory adaptive management treatment group, with those receiving only a standard lecture, relative to placebo controls. Using a within-subjects pretest-posttest control design, changes in ecological knowledge, environmental beliefs, attitudes, norms, and behavioral intentions were evaluated. Participants in adaptive management retained more knowledge of ecological topics after a period of 8 months compared to those receiving a standard lecture, both relative to controls. Involvement in adaptive management was also the only treatment that altered personal norms and beliefs related to stocking. Critically, only the stakeholders who participated in adaptive management reduced their behavioral intentions to engage in fish stocking in the future. Adaptive management is essential for robust ecological knowledge, and we show that involving stakeholders in adaptive management experiments is a powerful tool to enhance ecological literacy and build environmental capacity to move toward sustainability. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders.

Toybox's Adaptive Management in Practice - Malcolm, Emily (Toybox, 2017)
At Toybox, we understand ‘Adaptive Management’ as a broad innovative and learning approach that involves the whole organisation, our partners and funders. ‘Adaptive Programming’ of projects is part of this approach which is greatly enhanced by the Adaptive Management of all actors, including communities and children in the projects. Over the last few years Toybox have been piloting Adaptive Programming with our partners across Latin America, Africa and Asia to support children in street situations. This project has been developed within the wider context of an organisation which is focused on innovation and learning, therefore enabling Adaptive Management to become mainstream within the organisation. This paper captures the experiences and learnings of Toybox to our newly implemented Adaptive Programming approach, through the lens of a small-sized UK-based organisation working with local organisations internationally. This paper explains our learnings, inclusive of why we believe Adaptive Management is important to Toybox and how the organisation has embraced this new approach.

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (MAVC Research Report, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Adaptiveness through ‘simplest tools and practices’ - Prieto Martin, Pedro (Institute of Development Studies, 2017)
In recent years, more and more influential development organisations have been openly recognising the central role that adaptive management capacities – the ability to keep improving strategies and actions as programmes unfold – play for the success of complex interventions. As a result, there has been a rich exchange of ideas and experiences on how to promote adaptiveness in development. But development organisations and professionals are having a hard time translating the many adaptive theories and recommendations into improved practices and outcomes. They are generally failing to adjust the design and operation of programmes to accommodate incipient lessons learnt and the unexpected changes in the context. Nowadays, most programme adaptations still take the form of a change of direction once it is clear that things have gone really wrong. Why is so difficult to put what we know about adaptiveness into practice? And more importantly: what can be done to improve this situation?

Bridging Real-Time Data and Adaptive Management in International Devepment - Case Study Report - Ramalingam, Ben; Barnett, Inka; Valters, Craig; Oppenheimer, Carrie; Levy, Anna; Hernandez, Kevin (IDS, 2017)

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2017 update) - Learning Lab (USAID, 2017)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Six things that help grant-makers learn and adapt - Murray, Aoife (Itad, 2017)
There’s an emerging body of literature identifying key strategies that can both improve learning and enable adaptive management amongst grant-makers. We recently reviewed a host of publications from eight grant-making organisations. Those organisations have diverse aims and approaches but we’ve identified six common themes that stand out: Strong leadership and facilitation enables successful learning and …

Interview protocol: Most significant turning points - Prieto Martin, Pedro; Faith, Becky (Institute of Development Studies, 2017)
This interview protocol was used for a research project on adaptiveness in technology for governance initiatives in Kenya. For more information, please read the research report at: Prieto Martin, P.; Hernandez, K.; Faith, B. and Ramalingam, B. (2017) Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya, MAVC Research Report, Brighton: Institute of Development Studies, ids.ac.uk/project/making-all-voices-count
Keywords: IMPORTANT

Fostering Learning in Large Programmes and Portfolios: Emerging Lessons from Climate Change and Sustainable Development - Harvey, Blane; Pasanen, Tiina; Pollard, Alison; Raybould, Julia (Sustainability, 2017)
In ﬁelds like climate and development, where the challenges being addressed can be described as “wicked”, learning is key to successful programming. Useful practical and theoretical work is being undertaken to better understand the role of reﬂexive learning in bringing together different knowledge to address complex problems like climate change. Through a review of practical cases and learning theories commonly used in the areas of resilience, climate change adaptation and environmental management, this article: (i) reviews the theories that have shaped approaches to reﬂexive learning in large, highly-distributed climate change and resilience-building programmes for development; and (ii) conducts a comparative learning review of key challenges and lessons emerging from early efforts to promote and integrate reﬂexive learning processes in programmes of this nature. Using a case study approach, the authors focus on early efforts made in four large, inter-related (or nested) programmes to establish, integrate and sustain learning processes and systems. Eight themes emerged from the review and are considered from the perspective of learning programmes as emergent communities of practice. By investigating how these themes play out in the nested programming, the paper contributes to the limited existing body of evidence on learning in large climate change programmes and identiﬁes areas where future efforts might focus.

Donor perceptions and processes: Risks to success of adaptive programming? - Browse - Knowledge Platform Security & Rule of Law - Donovan, Elbereth (Knowledge Platform - Security & Rule of Law, 2017)
Keywords: IMPORTANT

How can we be more adaptive? AdaptScan identifies critical areas for improvement - Mercy Corps (Mercy Corps & IRC, 2017)
Keywords: IMPORTANT

Adaptive Programming and Business Environment Reform – Lessons for DFID Zimbabwe - Donovan, Elbereth; Manuel, Clare (DFID, 2017)
Keywords: IMPORTANT

Learning, monitoring and evaluating: achieving and measuring change in adaptive programmes - Callaghan, Sarah; Plank, Georgia (Synthesis Paper, 5, 2017)

Re-Perceiving Results: Aid Programs and Change in Fragile Societies - van Veen, Erwin; Rijper, Alies (Policy Brief, 2017)
Aid programmes need to be able to adapt their objectives and operations to changes in their political environment, since development processes are subject to political contestation. Change takes time and is often a matter of seizing the opportunity.
Keywords: IMPORTANT

Extreme Teaming: Lessons in Complex, Cross-Sector Leadership - Edmondson, Amy C.; Harvey, Jean-Francois (Emerald Publishing, 2017)
Extreme Teaming Lessons in Complex, Cross-Sector Leadership Today’s global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today’s global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries – that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.

Transformation, politics and implementation: smart implementation in governance programs - Kirsch, Renate; Siehl, Elke; Stockmayer, Albrecht (Nomos, 2017)
Working in environments characterised by a high degree of uncertainty, uncontrollability and unpredictability, development agents try to organise complex realities into manageable units. What principles influence the decision on adequate approaches and necessary steps? Through theoretical considerations and nine case studies, the GIZ traces implementation processes and identifies underlying guiding principles which provide the flexibility and adaptability that is necessary for acting in complex contexts. Main findings show that an adaptive and reflexive management structure is crucial for successful implementation. Quick iteration and tight feedback loops facilitate adaptation and reorientation. Contextsensitive knowledge and constant monitoring create a space for learning and innovation. A joint vision for the future which is used for orientation purposes and can be modified according to new findings and developments fosters fruitful cooperation.

USAID ADS 201 - Program Cycle Operational Policy (Update 1/23/2017) - USAID (USAID, 2017)
The Program Cycle is USAID’s operational model for planning, delivering, assessing, and adapting development programming in a given region or country to advance U.S. foreign policy. It encompasses guidance and procedures for: 1) Making strategic decisions at the regional or country level about programmatic areas of focus and associated resources; 2) Designing projects and supportive activities to implement strategic plans; and 3) Learning from performance monitoring, evaluations, and other relevant sources of information to make course corrections as needed and inform future programming.

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Mediation Practice Series, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Rapid experiments with a purpose - Moses, Michael (BEAM Exchange, 2017)
New insights, opinions and perspectives on market systems development, from experts and practitioners.
Keywords: IMPORTANT

Using what we know: How to ensure tech projects meet the brief - Walker, Tom (Making All Voices Count, 2017)
Making tech effective - building on what we already know

A ‘real-time’ and anthropological response to the Ebola crisis - IDS (IDS, 2017)
Impact Summary The Ebola epidemic that began in the Guinea-Sierra Leone-Liberia border region in December 2013 spread fast through the villages, cities and trade routes of this highly-peopled,...

Is there a new Washington Consensus? An analysis of five World Development Reports - Evans, Alice (From Poverty to Power, 2017)
Is there a new Washington Consensus? Alice Evans analyses the last five World Development Reports and finds significant changes in orthodoxy, but also big gaps

Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.

RFI-521-17-000015 - Improving Governance in Haiti Program (IGHI) - USAID (USAID, 2017)

The Boda Boda Talk Talk Module - Internews (Learning Collection, 2017)
Keywords: IMPORTANT

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

ADS 201 Additional Help- Whole-of-Project Evaluation - USAID (USAID, 2017)

Teams that Do Development Differently - Khan, Jehanzeb; Fisher, Annette (Global Policy Journal, 2017)

Scenario-based strategizing: Advancing the applicability in strategists' teams - Lehr, Thomas; Lorenz, Ullrich; Willert, Markus; Rohrbeck, René (Technological Forecasting and Social Change, 2017)
For over 40years, scenarios have been promoted as a key technique for forming strategies in uncertain environments. However, many challenges remain. In this article, we discuss a novel approach designed to increase the applicability of scenario-based strategizing in top management teams. Drawing on behavioural strategy as a theoretical lens, we design a yardstick to study the impact of scenario-based strategizing. We then describe our approach, which includes developing scenarios and alternative strategies separately and supporting the strategy selection through an integrated assessment of the goal-based efficacy and robustness. To facilitate the collaborative strategizing in teams, we propose a matrix with robustness and efficacy as the two axes, which we call the Parmenides Matrix. We assess the impact of the novel approach by applying it in two cases, at a governmental agency (German Environmental Ministry) and a firm affected by disruptive change (Bosch, leading global supplier of technology and solutions).
Keywords: Behavioural strategy; Scenario-based strategizing; Scenarios; Strategic foresight; Uncertainty

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Governance Working Paper 1, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

DFID Smart Rules: Better Programme Delivery - version VII (2017.04) - DFID (DFID, 2017)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice